Theorizing Medieval Visual Art by Means of Information and Communication Sciences - Cailloux, Marianne (Actual Problems of Theory and History of Art, 2022)
For about thirty years now, transdisciplinarity revitalised the history of art almost completely: cultural and visuall studies, and among them French Visual Anthropology has brought cultural history within iconographic and stylistic analysis.The aim of this paper is to offer some thoughts about innovation in the approach of Art History with a particular reflexion on if et how it is possible to bring about visual arts theory and cultural history through the prism of information and communication sciences, by experimenting this way of analysing on late Middle Ages occidentale images. This communication intends to fit in the thematic section studying medieval and early modern art from an interdisciplinary theorisation and methodology of research. It dwells on the break-through offered by the works of Hans Belting and Jean-Claude Schmidt, but also reflecting on artefacts issues about power (Freedberg), performativity (Bartholeyns and Golsenne) and agency (Gell).First, we will see an artistic image can be understood as an audio-visual socio-cultural “dispositive”, instead of just apprehend them as stylised representations. There is indeed a completing and cumulative aspect in the semantic links between liturgy, architecture, and iconography. The image builds itself as transitive dispositif of cultural and informational contents (Jeanneret, 2008), that can be experimented as a cognitive semiotic system (Régimbeau, 2007). Then, we will question multimodality and agency for ancient images, based on information reception theory from the “spect-actor”, rather than comparative and attributive approach of artefacts producers, like in classic art history. The goal here is to investigate uses and purposes, rather than functions. We can see that the receiver of an image establishes a complex individual relationship with it, which stratification can be decoded through rational relations, symbolic investments and cathartic emotional responses that are all often operating in this precise time period of the Middle Ages. This can put into perspective networks, communication and information circulations and see producers, patterns, and ideas as transcultural and transmissive carriers (Mucchielli, Corbalan et Ferrandez, 2004; Proulx, 2015).
Keywords: wall painting; Alps; visual studies; religious iconography; agency